Mao's China and Sino-Soviet Split : Ideological Dilemma. - Li, Mingjiang (Routledge contemporary China series., 2012)
The Sino-Soviet split in the 1960s was one of the most significant events of the Cold War. Why did the Sino-Soviet alliance, hailed by its creators as "unbreakable", "eternal", and as representing "brotherly solidarity", break up? Why did their relations eventually evolve into open hostility and military confrontation? With the publication of several works on the subject in the past decade, we are now in a better position to understand and explain the origins of the Sino-Soviet split. But at the same time new questions and puzzles have also emerged. The scholarly.